4D Multimaterial Printing of Programmable and Selective Light‐Activated Shape‐Memory Structures with Embedded Gold Nanoparticles. Issue 5 (1st October 2021) - Wang, Yu; Sachyani Keneth, Ela; Kamyshny, Alexander; Scalet, Giulia; Auricchio, Ferdinando; Magdassi, Shlomo
Abstract: 4D printing is based on 3D printing of objects that can change their shape upon a proper triggering. Here, a novel approach is reported for fabricating programmable 3D printed objects composed of shape‐memory polymers (SMPs) that are activated by light. The light activation of the movement and shape morphing are based on combining gold nanoparticles (AuNPs) as photothermal converters with acrylate‐based printing compositions that form an SMP with tunable transition temperatures. The shape change of the printed objects is triggered by remote irradiation with a low‐cost LED light at a wavelength specific to the surface plasmon resonance of the embedded AuNPs. The light is converted to heat which enables the shape transition when the temperature reaches the T g of the polymer. Excellent SMP properties are achieved with shape fixity and recovery ratios over 95%. This material composition and triggering approach enable fabricating programmable light‐activated 3D printed structures with a dual transition while tuning the concentration. Furthermore, numerical simulations performed by finite‐element analysis result in the excellent prediction of the shape‐memory recovery. The presented approach can be applied in remotely controlling morphing, mainly for applications in the fields of actuators and soft robotics. Abstract : 3D printed shape‐memory polymer (SMP) objects are remotely activated by light at a specific wavelength. The light activation occurs due to embedded photothermal converters, gold nanoparticles (AuNPs), triggering the actuation of the thermoresponsive SMP. By tuning the glass transition temperature of the thermoresponsive SMP and concentration of AuNPs, multimaterial 4D printed structures are fabricated.